L' attività scientifica e didattica di Anna Talamanca: la forza della mitezza, la dolcezza del rigore - Angeletti, Silvia (Il diritto ecclesiastico, 2024)
The teaching and research activity of Anna Talamanca. The strength of meekness, the kindness of rigor · This essay honors the teaching and research activity of the law and religion professor Anna Talamanca. Briefly sketching her biography and professional history, the essay will highlight the strands of research covered by Talamanca and her academic and human legacy to law and religion scholars.